Implementasi Scratch dalam Membangun Kompetensi Pemrograman di SMP NU Kaligesing, Purworejo - Ummi, Farkhatul (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the implementation of scratch in building programming competencies at SMP NU Kaligesing, Purworejo. Scratch, as a visual programming language designed to make it easier for beginners, is expected to help students develop an understanding of basic programming concepts through an interactive and fun approach. This study uses a qualitative method with an interview approach and literature review. The results of the study show that the use of Scratch is effective in improving students' basic programming competencies, especially in the aspects of logic, algorithms, and creativity. In addition, students show high enthusiasm during the learning process due to the intuitive visual scratch interface and support the development of interesting projects. Scratch plays an important role in improving the programming skills of students at SMP NU Kaligesing, Purworejo with a visual approach that is easy to understand, but still intellectually challenging. The use of Scratch can be an effective learning model in schools even with limited resources.